PENGARUH RADIASI SINAR GAMMA TERHADAP KULTUR IN VITRO TANAMAN JAHE - Devy, Lukita; Sastra, Dodo R (Jurnal Sains dan Teknologi Indonesia, 2006)
In vitro shoot explants of white ginger and red ginger are irradiated by two different techniques. The first, the tuber explants are irradiated by 2 levels of gamma rays namely 10 and 30 Gy. The second, the shoot explants are irradiated by 2 levels of gamma rays namely 7,5 and 12,5 Gy. The irradiated explants are regenerated on modified MS medium with BAP 2 ppm and NAA 0,25 ppm. The result show that the irradiated tuber explants with 10 and 30 Gy could not initiate new regenerant of ginger. On the other hand the irradiated shoot explants with 7,5 and 12,5 Gy have been able to influence the growth and development of shoot, leaf and root. It is indicated that the level of gamma rays irradiation on shoot explants influences the induced putative mutant of ginger. However, the sprouting of red ginger on 12,5 Gy is higher and faster than 7,5 Gy, and white ginger as well as control. The other morphological characters have not been able to be identified, the experiment are still in process to detect the mutagenic influences.